Image operators : image processing in Python - Kinser, Jason M., 1962- (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2018)
This book will provide a unified theoretical foundation of image analysis procedures with accompanied Python computer scripts to precisely describe the steps in image processing applications. Linkage between required scripts and theory through operators will be presented. Readers will be able to quickly write computer code to correctly implement the algorithms. Chapters will contain theories, operator equivalents, examples, Python codes, and exercises. Python downloads will be available--
Part I -- Image Operators -- Operator Nomenclature -- Scripting in Python -- Digital Images -- Color -- Part II Image Space Manipulations -- Geometric Transformations -- Image Morphing -- Principle Component Analysis -- Eigenimages -- Part III Frequency Space Manipulations -- Image Frequencies -- Filtering in Frequency Space -- Correlations -- Part IV Texture and Shape -- Edge Detection -- Hough Transforms -- Noise -- Texture Recognition -- Gabor Filtering -- Describing Shape -- Part V Basis -- Basis Sets -- Pulse Images and Autowaves.
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
OCLC-licensed vendor bibliographic record.
Keywords: Image processing -- Digital techniques; Python (Computer program language); COMPUTERS / General; TECHNOLOGY / Imaging Systems; TECHNOLOGY / Electricity; MATHEMATICS / Arithmetic